2020
DOI: 10.1371/journal.pone.0244594
|View full text |Cite
|
Sign up to set email alerts
|

Tactile information counteracts the attenuation of rubber hand illusion attributable to increased visuo-proprioceptive divergence

Abstract: Sense of body ownership is an immediate and distinct experience of one’s body as belonging to oneself. While it is well-recognized that ownership feelings emerge from the integration of visual and somatosensory signals, the principles upon which they are integrated are still intensely debated. Here, we used the rubber hand illusion (RHI) to examine how the interplay of visual, tactile, and proprioceptive signals is governed depending on their spatiotemporal properties. For this purpose, the RHI was elicited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
(121 reference statements)
1
7
0
Order By: Relevance
“…Crucially, our additional hypothesis was not confirmed, as we did not find evidence of a positive association between one’s sensitivity to walking speed changes and propensity to perceive optimally paced optic flows during binocular rivalry. This result is actually in line with our previous studies (in the domain of multisensory conflicts), which found no evidence for the relatively stronger impact of proprioception with increasing reliability of proprioceptive signals—independently of whether the assessments were based on the detection of passive limb displacement (Litwin et al., 2020) or active reproduction of joint position (Motyka et al., 2021; Motyka & Litwin, 2019). A generalized interpretation of such observations might appeal to the overall inferiority of proprioceptive acuity in relation to the acuity of other exteroceptive modalities (e.g., vision).…”
Section: Discussionsupporting
confidence: 91%
“…Crucially, our additional hypothesis was not confirmed, as we did not find evidence of a positive association between one’s sensitivity to walking speed changes and propensity to perceive optimally paced optic flows during binocular rivalry. This result is actually in line with our previous studies (in the domain of multisensory conflicts), which found no evidence for the relatively stronger impact of proprioception with increasing reliability of proprioceptive signals—independently of whether the assessments were based on the detection of passive limb displacement (Litwin et al., 2020) or active reproduction of joint position (Motyka et al., 2021; Motyka & Litwin, 2019). A generalized interpretation of such observations might appeal to the overall inferiority of proprioceptive acuity in relation to the acuity of other exteroceptive modalities (e.g., vision).…”
Section: Discussionsupporting
confidence: 91%
“…The greater the spatial visuoproprioceptive conflict is, the weaker the illusion (Lloyd, 2007;Kalckert & Ehrsson, 2014;Chancel & Ehrsson, 2020;Fan et al, 2021). Notably, the influence of proprioceptive precision (i.e., reliability) on the body ownership percept elicited in the rubber hand illusion has recently been questioned (Motyka & Litwin, 2019;Litwin et al, 2020), which is at odds with a Bayesian account of the sensory processes involved in body ownership (Litwin, 2020). However, in these studies, proprioceptive reliability was not experimentally manipulated but indirectly inferred in a separate hand localization task and used to investigate individual differences in illusion strength.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the visuo-tactile stimuli were applied at a higher frequency (approximately 0.5 Hz) compared to the visuo-vestibular stimuli (approximately 0.15 Hz), meaning that there were more bimodal events in the visuo-tactile correlations; thus, the information from the visuo-tactile correlations would provide more reliable information. Indeed, we know from a rubber hand illusion experiment that increasing the information content in visuo-tactile correlations boosts hand-ownership illusion during simultaneous visuo-proprioceptive conflict [ 65 ]. In our Bayesian causal model, less reliable visuo-vestibular information due to the artificial GVS stimulation or more reliable visuo-tactile information due to more visuo-tactile events in the correlations would be mathematically equivalent, leading to more reliable visuo-tactile estimates that therefore influence the overall body ownership estimate more than the less reliable visuo-vestibular estimates ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%